Which Dilemmas of Policy Making under Thatcher and Reagan can be Identified in the Transition Economies of 1990s? - Aleksandar Vasilev (Journal of Applied Economic Sciences, 2019)
The macroeconomic aspects of the transition experience in the early 90s were a great challenge. Different policy mixes were introduced, both on a country level and among the transition countries. Some of the programs shared similarities to Thatcher and Reagan packages for economic recovery. There was no clear-cut answer to the question of how to achieve macro-stabilization in a transition environment: to implement supply-side or demand-side policies, micro reforms or macro reforms first. Blindly relying on theory or other countries' policies could be damaging. That is why historical experience has to be taken with caution and tailored to the specific environment in the particular country.
Keywords: P21; 330; policy dilemmas; Thatcher; Reagan; transition economies